Learning the ropes - Naylor, Sharon; Ferguson Publishing (New York : Ferguson, 2009)
'Understanding what to expect from the first day on the job and how to successfully navigate the workplace environment can help ease a challenging transition. Learning the Ropes, Third Edition tackles the difficult subject of how to fit into a new context, whether at work or at school.'--Publisher's web site
Rev. ed. of : Learning the ropes / Sharon Naylor, 1998
Includes bibliographical references (p. 157-160) and index
Keywords: Vocational guidance -- Juvenile literature; Work -- Juvenile literature; Vocational guidance; Work